Gamma Rays of Tellurium-131 and Tellurium-129 - Mallmann, C. A.; Aten, A. H. W.; Bes, D. R.; de Mallmann, Clara M. (American Physical Society, 1955)
Fil: Mallmann, C. A. Comisión Nacional de Energía Atómica; Argentina